KAJIAN SUHU PENGOVENAN TERHADAP KADAR PROTEIN DAN NILAI ORGANOLEPTIK TELUR ASIN - D. Novia; S. Amelia; N. Z. Ayuza (Jurnal Peternakan, 2011)
Salted eggs are a source of animal protein foods suitable for children, adolescents, parents, people in the healing periodand pregnant women. This study aimed to determine the effect of oven temperature on protein content and taste of saltedeggs. This study uses pesisir duck eggs (Indian Runner) fresh 48 hour maximum age of 200 items weighing 65-70 g obtainedfrom a breeder in Anduring Padang, 3000 grams of brick powder, gray rub 2000 grams and 1000 grams of salt. Researchmethod used is the method of experiment with Random Design Group (RAK), which consists of 4 treatments and 5 groups asreplicates. Treatment A (oven temperature 70ºC), B (oven temperature of 80ºC), C (oven temperature of 90ºC) and D (oventemperature of 100ºC). Oven eggs done for 6 hours, then stored for 25 days. Observed variable is based on dry weight proteincontent and taste of salted eggs. The data obtained were statistically analyzed with F test, if influential followed by Duncan'stest. The results showed different effects very significantly (P<0,01) on texture, significantly different (P<0,05) proteinlevels, showing the influence of different flavors but not significant (P>0,05) to the aroma of salted eggs. Based on theresearch results can be concluded that the oven temperature best eggs after 25 days of storage is at a temperature of 90ºC witha 37,00% protein content, taste 2,47 (like), aroma 2,38 (neutral) and texture 2,66 (like).